Psychological Status of Opioid Treatment Service Staff in Tehran, the Epicenter of COVID-19 Outbreak in Iran: A Longitudinal Cohort Study - Bijan Pirnia; Hasan Mosazadeh; Babak Lotfi; Fariborz Pirnia; Kambiz Pirnia; Parastoo Malekanmehr (Golestan University of Medical Sciences, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a severe acute respiratory syndrome that emerged in early December 2019. Global proliferation, abrupt increases in confirmed cases, and the risk of self-infection have caused significant stress and anxiety among staff working in opioid treatment services (OTS). The aim of our study was to determine the psychological status of staff working in OTS during the outbreak period of COVID-19 in Tehran.  Methods: In a short-term longitudinal survey, 621 staff members, including physicians, psychologists, nurses, and social workers, who were selected using probability-based online panel. Data was gathered using online questionnaires including the Patient Health Questionnaire-4 (PHQ-4), the Brief Fatigue Inventory (BFI), and the Jenkins Sleep Scale (JSS). Longitudinal assessment of anxiety, depression, fatigue and sleep problems in three periods including pre-outbreak, outbreak, and non-epidemic outbreak was done through the online panel. Data were analyzed by paired t-test and repeated measures correlation. Results: The rates of anxiety, depression, fatigue, and sleep problems of the staff working in OTS during the outbreak period were significantly higher than that of the pre-outbreak period (P<0.001), and it remained significantly higher during the non-epidemic outbreak and did not decrease significantly (P>0.05). The correlation coefficient between the anxiety, depression, fatigue, and sleep problems was significant in all three periods and the highest correlation was in the outbreak period (P<0.001). Conclusion: Mental health problems of staff were common during the outbreak of COVID-19. Mental health problems of staff can limit the effectiveness of addiction treatment programs in the long time.